Peningkatan Kemampuan Adaptasi Lingkungan Internal dan Eksternal dalam Mendukung Perbaikan Manajemen Usaha Mikro di Kabupaten Sidoarjo - Artaya, I Putu; Kamisutara, Made; Arimbawa, I Gede (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
To increase the ability of micro businesses to compete and develop, strength is needed in adapting to the internal and external environment. For this reason, it is necessary to improve their managerial abilities in controlling the environment in a focused manner. For this reason, expertise and strength are needed to adapt to the internal and external environment. To prove this, a survey was conducted on 43 samples of micro business actors in four sub-districts in Sidoarjo Regency, East Java with a total population of 1,020 business units. The four sub-districts include Prambon, Porong, Jabon and Krembung. Based on the results of data and information collection in the four sub-districts, the results showed that micro business actors have weaknesses in three main areas in the process of developing their business management, namely 8.77% are unable to collaborate with business mitra usaha, 12.39% are less able to implement sales networks , and the last 23.62% problem is inability or lack of expertise in utilizing technological advances in developing businesses. Four sub-districts were chosen because they have the highest number of micro business activities compared to other sub-districts. The data collection process is via Microsoft Forms which can be operated via instant messaging through communities and business communication media. To overcome the three main obstacles above, continuous synergy and training is needed from related parties which includes business management development training, training on cooperation opportunities with business mitra usaha, and training on technology adoption that supports business processes. These 43 micro business actors have innovation value from the products they produce and can be developed further to improve their business. Their products consist of packaged food products, clothing products, craft products, herbal or health products, and beverage products